Transformation of Indang Arts: from Dakwah to Prestige and Commodification - Nurwani Nurwani; Martozet Martozet (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to find out how the transformation contained in Indang art. The transformation of Indang art seen from the function includes three things, namely from da'wah to prestige, and commodification. In order to find out the transformation of Indang art, a search was carried out using qualitative methods. Data collection was carried out by direct observation, interviews and documentation to art actors and owners. Indang art originally functioned as a medium of da'wah, for the spread of Islam, which was carried out from surau to surau. However, after this art began to be in demand by the people in Pariaman, it began to be displayed in open spaces or matches. Indang art that is displayed in the matches began to be contested by holding a test of insight, agility and agility of movements, as well as the beauty of the songs or songs that were performed. In addition, each group often does a mental ability test, so each group must have a parent, called sipituang sirah who can guard and fence the group with mysticism. This art has changed its function from a religious propaganda media, to a prestige to raise self-esteem and honor for the winning group, both individually and in groups, as well as the Nagari community that owns Indang. When you are able to beat your opponent, you will feel proud, increase self-esteem, and honor. Feeling superior to the losing group and society. Currently, Indang art has undergone a change in function to become a market commodity that has economic value that has a selling value. The change in function into a commodity is able to defeat the previous values in the Nagari community, which owns Indang art.